The Cookies Club (Cookies Business) / Hidayati Sufiah Roslan - Hidayati Sufiah, Roslan (2020)
The Cookies Club is where authentic cookies’ lovers supposed to be. This is because we offer variety type of freshly baked cookies. All the cookies that we provide are made using our own unique recipe. That is what made our cookies are the best in town. The concepts for our business are, we making our own product which is the cookies and we selling it. Customer can buy it at our shop or order it online. We also provide services such as goodies bag service for event planner and delivery service for the customer. The product that we offer for this business are variety type of freshly baked cookies. Here are some of them; chocolate chip cookies, sea salt cookies, oatmeal cookies, brownies cookies and red velvet cookies. We’re also selling brownies. In the future, we would like to add more type of cookies and dessert to our menu. But the main product for our business is forever going to be the cookies. We are selling our product to the customers and also to the food operator such as café, bakery and vendor shop. The customers can buy our product at our shop that is located in the middle of Ipoh Town near The Plan B. They also can order our product through our website and social media which is Instagram, Facebook, Twitter and WhatsApp. Other than selling our product, services that being offered by The Cookies Club is goodies bag service for event planner and delivery service for customers. We provide a service for event planner by making them goodies bag for events such as birthday party, wedding and many more. For delivery service, we have our own runner to deliver customer’s order straight to their door step. We’re targeting people that are a massive fan of cookies because that what The Cookies Club for. We also targeting people that lives in Perak especially Ipoh to buy our product. It is because we’re near to them. Next we also targeting young people like teenager and young adult because they have a big influence in media social. It is because we would be promoting our product more on social media. Other than that, we’re targeting food operator such as café, bakery and vendor shop. Last but not least we’re targeting event planner. For competitive advantage, The Cookies Club is the only business that are specialize in cookies in Ipoh area. So cookies’ lovers will come and buy with us. We’re also located at the strategic location which is in the middle of Ipoh Town so it is easy for people to come to our shop. The Cookies Club provide delivery service for our product, so the customer don’t have to worry to go out. They just need wait at their place. Other than that, we also have goodies bag service for event planner, so indirectly we already have a connection in business with event planner.